2005
DOI: 10.1007/s00417-005-1133-x
|View full text |Cite
|
Sign up to set email alerts
|

Does intravitreal triamcinolone acetonide-assisted peeling of the internal limiting membrane effect the outcome of macular hole surgery?

Abstract: Our data showed similar outcomes for patients with macular hole where ICG has been used when compared to patients where triamcinolone acetonide has been used for ILM peeling. Further study with longer follow-up and large series is warranted to assess the safety of the triamcinolone acetonide assisted ILM peeling in macular hole surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…In several studies, intraocular TA was used intraoperatively during pars plana vitrectomy to visualize the inner limiting membrane, epiretinal membranes and remnants of the vitreous base [207,214,219,220,236]. Yamamoto et al [216] found that using TA during vitrectomy may facilitate both the removal of the epiretinal membrane around the macular hole and the separation of the residual vitreous cortex from the retina in highly myopic eyes with retinal detachment.…”
Section: Clinical Studies: Ta As Medical Device (Vitrectomy)mentioning
confidence: 99%
“…In several studies, intraocular TA was used intraoperatively during pars plana vitrectomy to visualize the inner limiting membrane, epiretinal membranes and remnants of the vitreous base [207,214,219,220,236]. Yamamoto et al [216] found that using TA during vitrectomy may facilitate both the removal of the epiretinal membrane around the macular hole and the separation of the residual vitreous cortex from the retina in highly myopic eyes with retinal detachment.…”
Section: Clinical Studies: Ta As Medical Device (Vitrectomy)mentioning
confidence: 99%
“…Kimura et al [198] performed triamcinolone acetonide-assisted peeling of the internal limiting membrane [122,203,204] . Yamamoto et al [200] used intravitreal triamcinolone acetonide in 6 eyes during vitrectomy in highly myopic eyes with retinal detachment due to a macular hole.…”
Section: Pars Plana Vitrectomy Combined With Intravitreal Triamcinolomentioning
confidence: 99%
“…(2,8) Since then other studies have confirmed that TA-assisted ILM removal gives good results (figure 7D) (39)(40)(41) . Compared to ICG-guided ILM removal, a noncontrolled study indicates that TA has the same closure rate with significantly better visual results with no side effects (42) . Crystals of TA have been detected up until forty days post surgery with chromovitrectomy for MH surgery.…”
Section: Triamcinolone Acetonidementioning
confidence: 99%